Analysis of the Mechanical Behaviour of a Tube Confined within a Granular Medium - Sajid ZEMAM (Misan Journal of Engineering Sciences)
Abstract: Understanding the mechanical behaviour of confined cylindrical shells is essential for the long-term stability of geotechnical structures such as buried pipelines and well casings. These structures often experience lateral loading when embedded in granular materials or rock, resulting in complex solid-to-solid interactions. This study investigates the stability of a metallic tube confined within such media through a combination of experimental and numerical approaches. A laboratory-scale test setup was developed to conduct controlled experiments on instrumented metallic tubes. The setup enabled the determination of the critical buckling pressure, identification of post-buckling stability loss, and monitoring of local deformations leading to failure. The study revealed that both nature (homogeneous vs. bi-material) and the stiffness of the confining medium significantly influence the critical buckling pressure and the angular extension of the single-lobe deformation pattern. Complementary finite element simulations were performed to interpret the experimental findings. The numerical results showed excellent agreement with the experimental data, validating the modelling approach. Simulations further provided detailed insights into the initiation and evolution of buckling prior to structural instability under increasing lateral confinement. These findings contribute to a deeper understanding of confined shell behaviour and have practical implications for the design and assessment of underground tubular structures.